The inclusion of the other in ourselves - Vieira, Ricardo (2018)
The intensification of different types of m igration movements during the last decades is an expression Of growing interconnections at the glabal level- The so called 'refugee crisis'is most visible sign of this intensification It currently challenges societies to rethink the >rocesses Of integrating fleeimg fram humanitarian crises and wars Portuguese civil society has pioneered the creation Of Refugee Support aimed to address the chadlenges associated with the arrival of refvgee families Within this platform, an e-learning course was created to help institutions and hast families prepare for this task- 1m the article we first describe this course, fotusing our analysis on the relevance of this initiative far institutions, families, and privatecitizens that wish to welcome refugees in Portugal. We then briefly reflect on the literature pertaining to intercultural dialogue and social tensions. In the final secficn we analysethe voices of those attended the course. We conclude with an analysis of the contents of the course modules and the participation Of the trainees a cont(ibutian to their self-transformation_